Noradrenergic-Specific Transcription of the Dopamine β-Hydroxylase Gene Requires Synergy of MultipleCis-Acting Elements Including at Least Two Phox2a-Binding Sites - Kim, Hee-Sun (J Neurosci, 1998)
Dopamine β-hydroxylase (DBH) catalyzes the conversion of dopamine to noradrenaline and is selectively expressed in noradrenergic and adrenergic neurons and neuroendocrine cells. Recent data from this laboratory showed that a paired-like homeodomain (HD) protein, Phox2a, interacts with the HD-binding site residing within a composite promoter of the human DBH gene, designated domain IV, in a cell-specific manner and directly controls noradrenergic-specific DBH promoter activity. In this report, we demonstrate that three additional protein-binding sites (i.e., domains I, II, and III) between domain IV and the TATA box are critical for intact DBH promoter activity in noradrenergic cells and that they activate DBH transcription in a highly concerted manner. Transient transfection assays of mutant DBH reporter constructs indicated that domain I was active in every cell line tested, whereas domain III was preferentially active in DBH-positive cells. Remarkably, mutation of domain II was associated with inactivation of DBH promoter activity exclusively in DBH-positive cell lines, defining it as another noradrenergic-specific promoter element. The cell-specific profile of the promoter function of these sequence motifs was further supported byin vitro DNA-binding studies and Southwestern analysis. Furthermore, competition and antibody supershift assays show that transcription factors Sp1 and AP2 are the cognate nuclear factors interacting with domains I and III, respectively. Parallel evidence indicates that domain II is another Phox2a-binding site, demonstrating at least two binding sites for this factor in the upstream DBH promoter. Strikingly, four tandem copies of domain II increased the promoter activity of a minimal DBH promoter by 100- to 200-fold in DBH-positive cell lines without compromising cell specificity. Cotransfection of Phox2a-expression vector dramatically increased the activity of the multiple domain II promoter only in DBH-negative cell lines, confirming that domain II is responsive to Phox2a. Collectively, this study emphasizes a critical role of Phox2a as well as its functional synergism with other transcription factors (e.g., CREB, AP2, and Sp1) in transcriptional activation of the DBH gene.